Structural Safety Analysis of Electromagnetic Levitation System Subject to Track Irregularities - Ni, Fei; Dai, Yawen; Shen, Boyang; Xu, Junqi (IEEE transactions on applied superconductivity, 2024)
In light of the cumulative impact of the stochastic track irregularity, ensuring optimal performance of the electromagnetic levitation system requires not only achieving robust operating performances but also sustaining high reliability over extended service periods. This paper conducts comprehensive research of the structural safety of the levitation unit within a Maglev train's levitation system and established an efficient first-passage analysis of the levitation unit by employing the probability density evolution method. This study explores the probability density evolution of the air gap subject to track irregularity excitation, providing insights into the impact of track irregularities on the first-passage time of the levitation unit.